El medio interno en la difteria - González, Hernán D. (1937)
The authours expound the results obtained in the study of the distinct modifications which exist, or which are pretended to exist in certain elements (urea, glucose, cholesterin, inorganic phosphorus, calcium, creatinine, pH) which enter into the composition of the blood of the diphtheric patients, arriving at the following conclusions: 1st The blood urea is found to be elevated with most frequency in common diphtheretic anginas, and complicated sub-malignant, and malignant cases. Within the same clinical form, when the figure is more elevated, the more serious is the process, without that one can say that a malignant form with less than one gram is of better prognosis than a common or sub-malignant form with more than this quantity. This is to indicate that the prognosis is conditioned by the clinical form and not by the ureal tenor. It is rare that the urea figure goes over 4 per thousand; and it happens iu the malignant form, and in circunstances in which this element is unnecessary as prognostic index. The other minor figures can normalize themselves, or without that, it signific that the patient will be cured. 2rd The glucose and cholesterin variations in the blood are not constant, nor they are intense or parrail el and they lack any prognostic value. They are the results of functional or organic disturbances of metabolism and not its cause, they do not correct themselves with the incorporation of glucose-insulin, not of cholesterin. 3rd Regarding calcium, inorganic phosphorus, and pH, one observes only small variations of the normal tenor without any prognostic value, the variations of creatinine are null. 4th There is hypochloremia in the acute period without any apparent relation with azotemia, which may be found elevated or not. 5th With all these preceding, it is inferred that only hyper-azotemia is of utility as a prognostic element and it has particular characteristic as in whatlisoever other process, without that of diphtheria.